THE IMPORTANCE OF DEVELOPING READING HABITS AMONG SCHOOL STUDENTS - Zuxriddin Meliboyev Isroil o’g’li (Modern American Journals, 2025)
This paper is centered on the importance of reading culture development among school children. With the existing speed of technological progress and digital distraction, students are reading less for knowledge acquisition and leisure. The paper takes into account some of the most important factors for the declining trend and suggests feasible options such as school reading programs, parental participation, and digital software to re-develop the reading culture. Results come from a series of classroom observations and surveys from several Uzbek schools, confirming that developing robust reading habits constructs academic success and emotional well-being.
Keywords: Reading habits, literacy, students, school reading programs, motivation, education in Uzbekistan.